Ethical Leadership and Employee Ethical Behaviour: The Mediating Roles of Ethical Climate and Organizational Identification in a Law Enforcement Institution - Retno Savitri; Corry Yohana; Christian Wiradendi Wolor (Indonesian Journal of Multidisciplinary Science, 2026)
Ethical behavior among employees is a critical issue in law enforcement institutions because unethical actions may undermine public trust, institutional legitimacy, and organizational accountability. Despite the implementation of ethical standards and oversight mechanisms, ethical violations remain a persistent challenge, highlighting the need to understand the organizational and individual factors that promote ethical conduct. This study aims to examine the effects of ethical leadership, ethical climate, and organizational identification on employee ethical behavior, while investigating the mediating roles of ethical climate and organizational identification. This research employed a quantitative explanatory approach involving 234 employees of an Indonesianlaw enforcement institution selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS4. The results demonstrate that ethical leadership, ethical climate, and organizational identification have positive and significant effects on employee ethical behavior. Furthermore, ethical leadership significantly influences ethical climate and organizational identification, while ethical climate also strengthens organizational identification. The mediation analysis confirms that ethical climate and organizational identification significantly mediate the relationship between ethical leadership and employee ethical behavior. These findings highlight that ethical behavior is shaped not only by individual awareness but also by ethical organizational systems and employees’ psychological attachment to institutional values. This study contributes to the ethical behavior literature by providing empirical evidence from a law enforcement context and offers practical implications for strengthening integrity-based leadership and organizational ethics.